Young people and the local redefinition of consumption - Paz, Sergio (Última Década, 2020)
This academic work seeks to tackle a discussion in progress about youth; consumption and space, starting by systemize some ideas about the linking between the transformation of the commercial offer and juvenile culture, and move forward in the analysis of their effects on the socio-economic local environments. In the context of the dynamics that define the reorganization of the metropolitan scenario in Buenos Aires, the larger recreational centers and malls deserve a special treatment since they have set themselves up as urban nodes that internalize resources that allow young people to classify themselves and classify the rest, as well as to produce a complete redefinition —locally characterized— of the consumption of these spaces and their merchandise. Architectonic design, music, decor, functional integration, special events, advertising incitation, ads, display of products, different aspects converging to give shape to the commercial atmosphere that we can find on the inside of these large commercial and recreational surfaces, where we can breathe the phenomenon of consumerism. An economical dynamic that acquires a complexity because of an active attitude on the part of young people who recreate the space they are submerged in, trough their social practices inside these spaces, generating a huge impact on the socioeconomic local systems.